Implementation Of Green Advertising Media To Influence Consumer Buying Behavior On Computer Product At Kelantan - Abdullah, Nurshawanis (UTeM, 2018)
For this research, the purpose is to implementation of green advertising in order to influence consumer buying behavior on computer product in Kelantan. The aim is to study how green advertising media will influence consumer buying behavior on purchasing computer product. This research use quantitative analysis by using questionnaires as the research instrument. This research involves 100 respondents which were students, workers and local resident that purchase computer product in rural areas. A total of 100 set of questionnaires using Likert Scale were will answered by respondents. All the answers and feed backs were been analyzed in details as the variables being the objectives of this research. All findings has been analyzed quantitatively. The data are collected and then analyzed using the IBM SPSS Statistics Version 23.0. This research also found four elements that are printed media, electronic media, digital interactive media, out-of-home media (IVs) towards consumer buying behaviour (DV). The results showed that most respondents choose digital interactive media as media that influence them in purchasing computer product. It is proved that the researcher has achieved all the research objectives in which there is a significant relationship between three independent variables with the dependent variable that influence them in purchasing computer product which are electronic media, digital interactive media and out-of-home media.